2005
DOI: 10.1071/mf04175
|View full text |Cite
|
Sign up to set email alerts
|

Tracking continental habitat shifts of eels using otolith Sr/Ca ratios: validation and application to the coastal, estuarine and riverine eels of the Gironde - Garonne - Dordogne watershed

Abstract: To enable a relevant interpretation of otolith strontium : calcium (Sr/Ca) variations in terms of habitat shifts of eels, the Sr/Ca-salinity relationship in eel otoliths was validated. Downstream and upstream migrations of young eels were reproduced in the laboratory by transferring groups of fish every 2 months between aquaria filled with water coming from the Dordogne river (salinity = 0), the upper Gironde estuary (salinity = 5), the lower Gironde estuary (salinity = 25) and the coast (salinity = 30), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 19 publications
6
88
0
Order By: Relevance
“…In recent years, microchemical analyses primarily focusing on strontium concentrations were frequently used to track individual migration pathways of wild caught eels (e.g. Tzeng et al 1997;Tsukamoto et al 1998;Limburg et al 2003;Arai et al 2004;Daverat et al 2005;Jessop et al 2006;Shiao et al 2006). The correlation between Sr/Ca ratios and ambient salinities is well established and the strontium content in otoliths is comparatively high and therefore easy to measure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microchemical analyses primarily focusing on strontium concentrations were frequently used to track individual migration pathways of wild caught eels (e.g. Tzeng et al 1997;Tsukamoto et al 1998;Limburg et al 2003;Arai et al 2004;Daverat et al 2005;Jessop et al 2006;Shiao et al 2006). The correlation between Sr/Ca ratios and ambient salinities is well established and the strontium content in otoliths is comparatively high and therefore easy to measure.…”
Section: Introductionmentioning
confidence: 99%
“…The tide carries them to the coast, where they transform, first into elvers and then small yellow eels that colonize growth areas. Some of them settle in coastal water and estuaries, but others colonize freshwater (Daverat et al, 2005). This growth stage commonly lasts from 1 to more than 15 years .…”
Section: Introductionmentioning
confidence: 99%
“…Representative case studies of Daverat et al (2005), Tzeng et al (2005), McCulloch et al (2005), Dorval et al (2005) and Hobbs et al (2005) demonstrated the utility of otolith chemistry in tracking movements and/or habitat shifts throughout the life history of fish, which, in turn, can be used to infer stock structure and population connectivity (Fowler et al 2005;Stransky et al 2005). Similarly, Gillanders and Joyce (2005) used otolith chemistry to differentiate aquaculture and wild-harvest yellowtail kingfish (Seriola lalandi), whereas Niva et al (2005) examined the effectiveness of alizarin-red-stained otoliths as a cost-effective mass-marking tool.…”
Section: Chemical Composition and Applications To Climate Ecology Anmentioning
confidence: 99%